Revisão crítica de técnicas para estudo de propriedades ácido-base de catalisadores heterogêneos - Shine, Luiza Sanae (Universidade Federal de São Carlos, 2022)
Currently, around 85% to 90% of all petrochemical and chemical industrial processes in large industries are catalytic. The insertion of catalytic steps makes the process more environmentally sustainable, as it leads to the formation of the desired product in less time, with less use of resources and generating less waste. A catalyst is a substance that increases the speed of a chemical reaction, decreasing its activation energy, without being consumed. When the catalyst is solid and the reactants are liquid or gaseous, the catalysis is heterogeneous. The physicochemical properties of the catalytic material influence its performance during the reaction. One of these properties is the acid-base character. To determine the acidity and basicity of a solid catalyst, there are several techniques. The Hammett indicators method is the simplest, indicating the presence of acidic or basic sites by the changing the color of the solution. It was initially developed for aqueous solutions and later extended to solids. Temperature programmed probe molecule desorption (TPD) and microcalorimetry are techniques based on the measurement of heat of desorption and heat of adsorption, respectively. The amount of heat released is associated with the strength of the active sites. Spectroscopy is based on the measurement of the transition energy between two levels, depending on the wavelength used. Nuclear magnetic resonance (NMR) spectroscopy measures the change in spin, while infrared spectroscopy (IR) measures the change in vibration. Both techniques provide information on adsorbed species, types and strengths of active sites. Model reactions lead to the formation of different products in acidic or basic medium, so the analysis of the products formed allows the quantification of acid or basic active sites. The objective of this work is to critically review these techniques and point out their advantages and disadvantages, associated with time, cost, simplicity, application and detailing of the surface characteristics of the material, and to present a possible association of techniques for a more complete study of acid-base properties of heterogeneous catalysts.
Critical review of techniques for studying acid-base properties of heterogeneous catalysts
Keywords: Catalisador; Catálise heterogênea; Propriedades ácido-base; Técnicas; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA